Comentario a la crónica del miliciano Orwell - Urbán Palacios, Víctor Manuel (THÉMATA. Revista de Filosofía, 2013)
En estas páginas trataré de acercarme a la trágica experiencia del combate, siguiendo principalmente el texto Cataluña 1937, en el que Orwell narra su paso por la milicia armada del POUM en el frente de Aragón, su participación en los Hechos de Mayo, la represión y encarcelamiento de los dirigentes trotskistas y su penosa salida del territorio republicano. In these pages I will try to approach the tragic experience of combat, mainly following the text Homage to Catalonia, in which Orwell narrates his way through the armed militia of the POUM in the Aragon Front, his participation in the Barcelona May Days, the repression and imprisonment of the Trotskyist leaders and his painful departure of Republican territory.